2022
DOI: 10.3389/fnut.2022.789833
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pre-pregnancy Body Mass Index Categories and Infant Birth Outcomes: A Population-Based Study of 9 Million Mother–Infant Pairs

Abstract: Background and AimsInfant adverse birth outcomes have been suggested to contribute to neonatal morbidity and mortality and may cause long-term health consequences. Although evidence suggests maternal prepregnancy body mass index (BMI) categories associate with some birth outcomes, there is no consensus on these associations. We aimed to examine the associations of maternal prepregnancy BMI categories with a wide range of adverse birth outcomes.MethodsData were from a population-based retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…10 In agreement with these findings, a larger study (9,282,486 mother-infant pairs in the USA) focussed on offspring outcomes indicated that higher maternal BMI was associated with higher risk of high birthweight, LGA, as well as low Apgar score and reported a nonlinear relationship with PTB risk. 36 Other observational studies using multivariable regression have reported that maternal BMI is associated with higher risk of stillbirths 37 , induction 38 , caesarean section 38 , and not initiating breastfeeding. 39 Previous Mendelian randomization studies have focused on a limited set of outcomes and are supportive of higher maternal BMI being related to higher mean offspring birthweight 4,40,41 (N ~ 9,000 to 400,000) and GDM 42 (N = 5,485 cases and 347,856 controls).…”
Section: Discussionmentioning
confidence: 98%
“…10 In agreement with these findings, a larger study (9,282,486 mother-infant pairs in the USA) focussed on offspring outcomes indicated that higher maternal BMI was associated with higher risk of high birthweight, LGA, as well as low Apgar score and reported a nonlinear relationship with PTB risk. 36 Other observational studies using multivariable regression have reported that maternal BMI is associated with higher risk of stillbirths 37 , induction 38 , caesarean section 38 , and not initiating breastfeeding. 39 Previous Mendelian randomization studies have focused on a limited set of outcomes and are supportive of higher maternal BMI being related to higher mean offspring birthweight 4,40,41 (N ~ 9,000 to 400,000) and GDM 42 (N = 5,485 cases and 347,856 controls).…”
Section: Discussionmentioning
confidence: 98%
“…Pre-pregnancy overweight and obesity are both associated with an increased risk of gestational hypertension and gestational diabetes 9,33 , which are associated with increased risk of induction of labour and/or planned caesarean section. This likely explains the increased risk of MPTB with higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Each birth weight percentile category was compared with the 50th–less than the 75th percentile category as a reference. Adjustments were performed for predetermined covariates: race, 22 ethnicity, 22 maternal age, 23 prepregnancy BMI, 24 chronic hypertension, 25 pregestational diabetes, 26 parity, 27 assisted reproductive therapy, 28 preeclampsia, 29,30 eclampsia, gestational hypertension, gestational diabetes mellitus (GDM), 31,32 chorioamnionitis, 33 steroids use, mode of delivery, 34 insurance type, 35 and neonatal sex. 36 Previous studies have shown that these factors could be associated with birth weight, infant mortality, or morbidity.…”
Section: Methodsmentioning
confidence: 99%